Genetic and morphological characterization of Acroceras macrum Stapf - Ferrari Usandizaga, Silvana Consuelo; Brugnoli, Elsa Andrea; Weiss, Alejandra I.; Zilli, Alex Leonel; Schedler, Mara; Pagano, Elba Maria; Martínez, Eric Javier; Acuña, Carlos Alberto (Wiley, 2019)
Acroceras macrum is a warm‐season grass used for pastures, and it has high nutritive value. The scarce genetic and reproductive information about this grass is limiting its breeding for forage. The objective of this research was to determine the number of genotypes and cytotypes present in a collection established in Argentina, and to estimate the diversity of this species based on molecular markers, and morphological and agronomic characteristics. The number of genotypes among forty‐seven accessions was determined using ISSR markers. The identified genotypes were further characterized for ploidy levels. In addition, the genetic distances among them were estimated with ISSR markers. They were also propagated and planted into the field following a randomized complete block design with four replications, and a group of sixteen morphological and agronomic variables were evaluated. A total of twenty‐seven genotypes were identified in this collection; twenty‐two genotypes were tetraploid (2n = 4x = 36) and five were hexaploid (2n = 6x = 54). These two cytotypes were found clearly separated by both genetic and phenotypic characteristics. Above‐ground biomass, internode length, initial growth and number of spikelets per inflorescence were the most variable traits. The high diversity present in this collection will allow for the initiation of a breeding programme for A. macrum.